Food for thought: Eating before saliva collection and interference with SARS‐CoV‐2 detection. Issue 6 (23rd February 2022) - Hernandez, Matthew M.; Riollano‐Cruz, Mariawy; Boyle, Mary C.; Banu, Radhika; Shrestha, Paras; Gray, Brandon; Cao, Liyong; Chen, Feng; Shi, Huanzhi; Paniz‐Perez, Daniel E.; Paniz‐Perez, Paul A.; Rishi, Aryan L.; et al.
Abstract: Saliva is a promising specimen for the detection of viruses that cause upper respiratory infections including severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) due to its cost‐effectiveness and noninvasive collection. However, together with intrinsic enzymes and oral microbiota, children's unique dietary habits may introduce substances that interfere with diagnostic testing. To determine whether children's dietary choices impact SARS‐CoV‐2 molecular detection in saliva, we performed a diagnostic study that simulates testing of real‐life specimens provided from healthy children ( n = 5) who self‐collected saliva at home before and at 0, 20, and 60 min after eating 20 foods they selected. Each of 72 specimens was split into two volumes and spiked with SARS‐CoV‐2‐negative or SARS‐CoV‐2‐positive clinical standards before side‐by‐side testing by reverse‐transcription polymerase chain reaction matrix‐assisted laser desorption ionization time‐of‐flight (RT‐PCR/MALDI‐TOF) assay. Detection of internal extraction control and SARS‐CoV‐2 nucleic acids was reduced in replicates of saliva collected at 0 min after eating 11 of 20 foods. Interference resolved at 20 and 60 min after eating all foods except hot dogs in one participant. This represented a significant improvement in the detection of nucleic acids compared to saliva collected at 0 min after eating ( p = 0.0005). We demonstrate successful detection of viral nucleic acids in saliva self‐collected by children before and after eating a variety of foods. Fasting is not required before saliva collection for SARS‐CoV‐2 testing by RT‐PCR/MALDI‐TOF, but waiting for 20 min after eating is sufficient for accurate testing. These findings should be considered for SARS‐CoV‐2 testing and broader viral diagnostics in saliva specimens. Highlights: Inconsistent collection and dietary habits impact viral nucleic acid detection in saliva. Various foods interfere with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) detection in saliva self‐collected by children. Waiting 20 min after eating is sufficient for accurate SARS‐CoV‐2 testing in saliva.